Atlantic Ocean Ventilation Changes Across the Last Deglaciation and Their Carbon Cycle Implications. Issue 2 (16th February 2021) - Skinner, L. C.; Freeman, E.; Hodell, D.; Waelbroeck, C.; Vazquez Riveiros, N.; Scrivner, A. E.
Abstract: Changes in ocean ventilation, controlled by both overturning rates and air‐sea gas exchange, are thought to have played a central role in atmospheric CO2 rise across the last deglaciation. Here, we constrain the nature of Atlantic Ocean ventilation changes over the last deglaciation using radiocarbon and stable carbon isotopes from two depth transects in the Atlantic basin. Our findings broadly cohere with the established pattern of deglacial Atlantic overturning change, and underline the existence of active northern sourced deep‐water export at the Last Glacial Maximum (LGM). We find that the western Atlantic was less affected by incursions of southern‐sourced deep water, as compared to the eastern Atlantic, despite both sides of the basin being strongly influenced by the air‐sea equilibration of both northern and southern deep‐water end‐members. Ventilation at least as strong as modern is observed throughout the Atlantic during the Bølling‐Allerød (BA), implying a "flushing" of the entire Atlantic water column that we attribute to the combined effects of Atlantic meridional overturning circulation (AMOC) reinvigoration and increased air‐sea equilibration of southern sourced deep‐water. This ventilation "overshoot" may have counteracted a natural atmospheric CO2 decline during interstadial conditions, helping to make the BA a "point of no return" in the deglacial process. While the collected data emphasize a predominantly indirect AMOC contribution to deglacial atmospheric CO2 rise, via far field impacts on convection in the Southern Ocean and/or North Pacific during Heinrich Stadial 1 and the Younger Dryas, the potential role of the AMOC in centennial CO2 pulses emerges as an important target for future work. Key Points: Increased ventilation ages occurred at all sites during the northern hemisphere stadials Heinrich Stadial 1, and the Younger Dryas The entire Atlantic was flushed with well‐ventilated waters at the onset of the Bølling‐Allerød Deglacial CO2 rise linked to abrupt releases from the Atlantic and more sustained release from the Southern Ocean and/or Pacific